ETHNICITY AND THE POLITICS OF STATE CREATION IN NIGERIA - Vande, Philip Terzungwe (European Scientific Journal, ESJ, 2012)
Political competitions and access to power, in plural societies like Nigeria, takes different forms and dimensions. Ethnic pluralism in Nigeria has more often than not been characterized by contestations and struggles for access to power and the resources of the Nation-State. Nigeria has therefore become a „cake. to be shared among the various nationalities, while nobody cares about the baking of the cake. The ethnic factor which initially ignited the demands for States creation has continued to torment the country. Thus, ethno-regional interests are usually mobilized to campaign for States creation and development and these agitations have been persistent and seemingly endless. This aim of this paper is to argue that the logic of continued States creation in Nigeria, purportedly to bring government closer to the people and achieve national development is a failed strategy. Again,the history and nature of States creation in Nigeria has failed to assuage the very forces that instigate the demands for new States. The prospects for national development and integration as well as local autonomy depend on the emergence of a purposeful, courageous, visionary and national leadership. Besides the leadership question, Nigeria needs a repositioned and strengthened local government system, an orientation to enable Nigerians on the need for peaceful co-existence and constitutional amendments to ensuring a true Federal system where the other levels of government will control a substantial amount of their resources.